National regulation and trade liberalization in services : the legal impact of the General Agreement on Trade in Services (GATS) on national regulatory autonomy /: the legal impact of the General Agreement on Trade in Services (GATS) on national regulatory autonomy. (2003) - Unknown
No abstract available